Development of a structured, evidence-based training framework for Traditional Birth Attendants in remote villages of Papua New Guinea - David, Sara Megan (Curtin University, 2023)
Qualitative Descriptive study to develop an evidence-based education framework for traditional birth attendants (TBAs) in low-resource settings of Papua New Guinea. Fifteen TBAs, ten Australian and Melanesian midwives were interviewed, their experiences interpreted using template analysis. Following review of TBA training globally, data was used to describe teaching content, methods and resources recommended for training TBAs. The Yamen TBA Education Framework was developed, a practical output to guide training of TBAs in Papua New Guinea.